Engendered or endangered? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Veronica De Klerk, Manager of Women's Action for Development in Namibia, participated at the Athens seminar on the Economic Role of Women in Rural and Agricultural Development the promotion of income-generating activities last October (see In...